Digital finance and financial literacy: An empirical investigation of Chinese households - Junhong Yang; Yu Wu; Bihong Huang (Asian Development Bank Institute (ADBI), 2020)
Using the 2015 and 2017 waves of the China Household Finance Survey (CHFS), we measured financial literacy and study its relationship to households' demand for digital finance. We found that a majority of households in the People's Republic of China possess limited financial literacy. The low levels of financial sophistication are responsible for the low usage of digital finance among Chinese households. Further, the positive impact of financial literacy on digital finance is more pronounced for wealthy, high-income, and young households, women, and households in urban and coastal areas. Our results are robust to using a variety of specifications and controlling for endogeneity, peer effects, cognition, and voluntary self-exclusion.
Keywords: D10; G11; D91; D83; 330; financial literacy; digital finance; household finance; CHFS; People's Republic of China